The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1471-2458-13-1038
|View full text |Cite
|
Sign up to set email alerts
|

Asthma prevalence and risk factors among children and adolescents living around an industrial area: a cross-sectional study

Abstract: BackgroundThe exposure to air pollution has negative effects on human health, increasing the risk of respiratory diseases, such as asthma. Few data are yet available on the epidemiology of childhood asthma in some areas of Italy. The aim of the study was to estimate asthma prevalence and related risk factors in children and adolescents residents around the industrial area of Termoli, Molise region, Central-South Italy.MethodsPrevalence was assessed through the administration of modified ISAAC questionnaires fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
7
3
1
Order By: Relevance
“…Unlike this study, our study revealed the importance of environmental factors, as in some other developing countries (20).…”
Section: Discussioncontrasting
confidence: 43%
“…Unlike this study, our study revealed the importance of environmental factors, as in some other developing countries (20).…”
Section: Discussioncontrasting
confidence: 43%
“…53.1% children (77, out of 145) had a family h/o Bronchial asthma. Many studies have shown strong correlation between positive family h/o atopy and bronchial asthma [22].…”
Section: Original Research Articlementioning
confidence: 99%
“…Asthma, a chronic respiratory disease, affects about 10% of adults and up to 30% of children. 1 , 2 Multiple demographic, environmental, and genetic factors, including sex, obesity, smoking history, exposure to air pollution, several genes in the lung development pathway, and family history, have been found to be associated with increased risk of asthma. 3 – 9 Asthma is inheritable, and many studies have found elevated risk associated with a positive parental history of asthma, positive first-degree relatives’ history of asthma, and the number of affected relatives.…”
Section: Introductionmentioning
confidence: 99%